ANALYSIS OF PETROLEUM TANKER FIRE AND EXPLOSION ACCIDENTS IN NIGERIA - Na’inna, Abdulmajid M.; Ani, Chukwuemeka L.; Kassimu, Abdullahi A. (FUDMA Journal of Sciences, 2025)
The menace of petroleum tanker fire and explosion accidents in Nigeria continues to increase in recent years with attendant consequences of loss of lives and properties. The present study performed a 16-year in-depth analysis of petroleum tanker fire and explosion accidents in Nigeria using secondary sources of data. It employed a mixed-method relating both qualitative and quantitative data collection and analysis techniques using 171 accident cases, 1822 deaths and 811 injuries. Year 2019 recorded the highest number of accidents of injuries as 29 and 178 respectively. However, the highest number of fatalities of 294 occurred in 2024. Also, the entire tanker accidents fall within “unacceptable” risk level in relation to societal risk curves. Five major aggravating factors namely mechanical, collision, impact, scooping and human were found to increase the severity of the accidents. Human factor accounted for both the highest number of accidents and injuries as 101 and 416 respectively, whereas, scooping of spilled petroleum products led to the peak number of fatalities of 730. Finally, an overview of the causes and aggravating factors of petroleum tanker accidents in Nigeria as well as the corresponding preventive/mitigative measures was given in Haddon Matrix. Regulatory agencies should strengthen tanker safety enforcement through rigorous vehicle inspection, driver training, and strict penalties for traffic violations. Public education campaigns must discourage fuel scooping. Investment in road infrastructure, emergency response systems, and pre-event preventive strategies, guided by the Haddon Matrix, is essential to reduce tanker fire and explosion risks.